Vehicle routing problem for multi-product cross-docking - GUNAWAN, Aldy (Institutional Knowledge at Singapore Management University, 2020)
Cross-docking is a logistic technique that can reduce costs occurred in a supply chain network while increasing the flow of goods, thus shortening the shipping cycle. Inside a cross-dock facility, the goods are directly transferred from incoming vehicles to outgoing vehicles without storing them in-between. Our research extends and combines this cross-docking technique with a well-known logistic problem, the vehicle routing problem (VRP), for delivering multiple products and addresses it as the VRP for multi-product cross-docking (VRP-MPCD). We developed a mixed integer programming model and generated two sets of VRP-MPCD instances, which are based on VRPCD instances. The instances are solved by a commercial software AMPL with CPLEX solver. The findings show that the small instances can be solved optimally by CPLEX. However, larger instances cannot be solved optimally within predefined computational times.